Writing for the New Yorker : critical essays on an American periodical - Green, Fiona; Green, Fiona (Edinburgh University Press, 2015)
This collection of newly commissioned critical essays reads across and between New Yorker departments, from sports writing to short stories, cartoons to reporters at large, poetry to annals of business. Attending to the relations between these kinds of writing and the magazine's visual and material constituents, the collection examines the distinctive ways in which imaginative writing has inhabited the 'prime real estate' of this enormously influential periodical. In bringing together a range of sharply angled analyses of particular authors, styles, columns, and pages, this book offers multiple perspectives on American writing and periodical culture at specific moments in twentieth-century history. Key Features:. Eleven new perspectives on major American writers, including Roth, Cheever, Plath, and Updike, in relation to their first publication contexts Reconsiders modern and contemporary American writing and periodical culture, focusing critical attention on commercially successful 'smart' magazines Draws on new research in The New Yorker's manuscript and digital archives A distinctive combination of close critical reading and cultural analysis